Long-term outcomes in patients diagnosed with bile-acid diarrhoea. Issue 2 (February 2016) - Lin, Simeng; Sanders, David S.; Gleeson, Joseph T.; Osborne, Christopher; Messham, Louise; Kurien, Matthew
Abstract : Objective: Bile-acid diarrhoea (BAD) is a recognized cause of chronic diarrhoea; however, its detection remains suboptimal. Currently, there is a paucity of follow-up studies evaluating BAD. This work evaluates the natural history of BAD by examining individuals diagnosed with BAD [7 days of 75 Se-homocholic acid taurine (SeHCAT) retention<10%] and determining the use of and response to bile-acid sequestrants (BAS). Materials and methods: Of the 515 patients, 40% (207/515) who underwent an SeHCAT test at Sheffield Teaching Hospitals (2001–2012) for chronic diarrhoea had BAD. Of the 207 (51%) patients, 107 were diagnosed between 2001 and 2009. In accordance with the guidelines, all of these patients were commenced on BAS. In March 2013, these individuals were reassessed either in the clinic or over the telephone as part of a local service evaluation project. Comparisons were made of both pretreatment and post-treatment variables using a Wilcoxon rank test. Results: Of the 107 patients, 54% (58/107) were followed up, with a median time since diagnosis of 6 years. Among them, 38% were still using BAS at follow-up, with 28% using alternative antidiarrhoeals. The median stool frequency decreased from seven stools per day to three ( P =0.0008) in those using BAS. The 34% of patients not receiving treatment had no change in their daily bowel frequency. The main reason for discontinuing treatment was poor tolerability of the BAS (colestyramine/colestipol). Conclusion: Our findings indicate that BAD is a chronic condition that best improves with BAS. Consideration should be given to therapeutic options that have a better tolerability profile.